DIFFICULTIES IN SPEAKING ENGLISH EXPERIENCED BY NON-ENGLISH MAJOR STUDENTS - Arifin, Muhammad Zainal; Muhayyang, Maemuna; Korompot, Chairil Anwar (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This research aims to discover the factors and ways students overcome difficulties in speaking English in non-English major students. This study used a descriptive qualitative research method, and the variables in this study are the factors of difficulty in speaking English and also how students overcome these difficulty factors. The subjects of this study were students from non-English major students, namely in the Indonesian Languages and Literature Education study program in 2023, with as many as 3 participants. The data of this study were obtained by conducting direct interview guidelines. The data analysis technique used is the interactive model of Miles, Huberman, and Saldana, including data condensation, data presentation (data display), and conclusions drawn. Based on the analysis, the results of the study show that non-English major students face difficulties in learning English due to challenges in vocabulary, grammar, pronunciation, fear, and lack of confidence. Overcoming these barriers requires a combination of strategies, such as utilizing online resources, practicing pronunciation, building confidence, and seeking support from peers and mentors. By adopting proactive measures and embracing a growth mindset, students can improve their English skills and overcome speaking difficulties effectively.